O papel dos assimilados, oprimidos e/ou emancipados nas lutas pela independ?ncia da Guin? Bissau no s?culo XX e os desafios para a educa??o - Vilela, Avelino (2024)
The study entitled ?The role of the assimilated, oppressed and,/or emancipated in the struggles for the Independence of Guinea Bissau in the 20th century and the challenges for education? aims to analyze the trajectory of the struggles for the independence of Guinea Bissau in the 20th century and the challenges for emancipatory education. The Guinean educational scenario and its public policies around education, together with the period of democratization of Guinea-Bissau (1991) until the beginning of the 21st century, allow us to establish relationships between social struggles for independence and the process of building a democratic society. In light of the concepts of ?assimilated,? ?oppressed,? and ?emancipated? in authors such as Franz Fanon, Paulo Freire, and Antonio Gramsci and reflections of Ucuni C?, we seek to discuss the history of Guinea Bissau. This research is qualitative and bibliographical (with an emphasis on history from the authors of Guinea Bissau with records of social struggles, groups, and leadership around the expressions of reorganization of the country from the emancipatory perspective of the 20th century). The initial interest in documentary research was impeded by the lack of access to national documents, leaving only the reference to the Constitution of the Republic (1996). At the end of the research, it can be inferred that the process and efforts of political emancipation that the assimilated, oppressed, and subalternate went through could not overcome the challenges of colonization for the transformation of education in Guinea Bissau.